Mexico : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This 2013 Article IV Consultation highlights that over the past year, Mexico has maintained macroeconomic policy continuity, while pursuing an ambitious agenda of growth-enhancing reforms. Reforms have already been approved to upgrade education, make labor markets more flexible, and foster competition in telecommunications. In 2013, the economy has begun to operate well below capacity, with real GDP growth expected to slow to 1.2 percent (down from 3.6 percent in 2012). The banking system-which accounts for about 60 percent of financial system assets-has remained resilient.